Hard Reading Learning from Science Fiction - Shippey, Tom (Liverpool Science Fiction Texts and Studies, 2016)
The fifteen essays collected in Hard Reading argue that science fiction has its own internal rhetoric, relying on devices such as neologism, dialogism, semantic shifts, the use of unreliable narrators. It is a "high-information" genre which does not follow the Flaubertian ideal of le mot juste, "the right word", preferring le mot imprévisible, "the unpredictable word". Science fiction derives much of its energy from engagement with vital intellectual issues in the "soft sciences", especially history, anthropology, the study of different cultures, with a strong bearing on politics. Both the rhetoric and the issues deserve to be taken much more seriously than they have been in academia, and in the wider world.Hard Reading is also a memoir of what it was like to be a committed fan, from teenage years, and also an academic struggling to find a place, at a time when a declared interest in science fiction and fantasy was the kiss of death for a career in the humanities.